Impact of High-Flow Nasal Cannula Use in Subjects With COVID-19 ARDS at High Altitudes: Clinical Presentation and Prognostic Factors. - Molano-Franco, Daniel; Viruez-Soto, Antonio; Gomez, Mario; Beltran, Edgar; Villabon, Mario; Sosa, Angela; Ortiz, Leidy; Orozco, Estefania; Hurtado, Alejandra; Sanchez, Lida; Arias-Reyes, Christian; Soliz, Jorge; et al. (Respiratory Care, 2024)
BACKGROUND: High-flow nasal cannula (HFNC) reduces the need for intubation in adult subject with acute respiratory failure. Changes in hypobaric hypoxemia have not been studied for subject with an HFNC in ICUs at altitudes > 2,600 m above sea level. In this study, we investigated the efficacy of HFNC treatment in subjects with COVID-19 at high altitudes. We hypothesized that progressive hypoxemia and the increase in breathing frequency associated with COVID-19 in high altitudes affect the success of HFNC therapy and may also influence the performance of the traditionally used predictors of success and failure. METHODS: This was a prospective cohort study of subjects >18 y with a confirmed diagnosis of COVID-19--induced ARDS requiring HFNC who were admitted to the ICU. Subjects were followed up during the 28 d of HFNC treatment or until failure. RESULTS: One hundred and eight subjects were enrolled. At admission to the ICU, ... delivery between 0.5-0.8 (odds ratio 0.38 [95% CI 0.17-0.84]) was associated with a better response to HFNC therapy than oxygen delivery on admission between 0.8-1.0 (odds ratio 3.58 [95% CI 1.56-8.22]). This relationship continued during follow-ups at 2, 6, 12, and 24 h, with a progressive increase in the risk of failure (odds ratio 24 h 13.99 [95% CI 4.32-45.26]). A new cutoff for the ratio of oxygen saturation (ROX) index (ROX 6 4.88) after 24 h of HFNC administration was demonstrated to be the best predictor of success (odds ratio 11.0 [95% CI 3.3-47.0]). CONCLUSIONS: High-altitude subjects treated with HFNC for COVID-19 showed a high risk of respiratory failure and progressive hypoxemia when ... requirements were > 0.8 after 24 h of treatment. In these subjects, personalized management should include continuous monitoring of individual clinical conditions (such as oxygenation indices, with cutoffs adapted to those corresponding to high-altitude cities).